(3TQM COH GdbGVis - (3GdNUGa , CMeO Hf YeQ Hf egjQ GdTjHGfj, CHh HcQ GdNUGa,J (B261 (3g` s ((3YHO GdQMef Hf CMeO Hf YcGTI GdCRejQj GdTGaYj s)
(3ChdgG (B:s
(3jHOC HHGH eG CHjM ddbGVi ef GdELJgGO s
(3BNQgG (B:s
(3jfJgj HHGH ai GdeQCI NGUe RhLgG ai hdO HCfg bO WdbgG s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ eaUd ddCHhGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdMOjK h GdeUWdMs